Experimental investigation on the heat transfer characteristics of supercritical CO2 at various mass flow rates in heated vertical-flow tube - Zhang, Shijie; Xu, Xiaoxiao; Liu, Chao; Liu, Xinxin; Dang, Chaobin (Applied thermal engineering, 2019)
•Experimental study is conducted on the heat transfer of SCO2 heated in vertical tube.•Heat transfer characteristics at the various mass flow rates have marked difference.•The mechanisms of deterioration are discussed at various mass flow rates.•A correlation is developed based on dimensionless parameters and experimental data. In this paper, experimental study is performed to investigate the characteristics of abnormal heat transfer of supercritical carbon dioxide (SCO2) at various ranges of mass flow rate in heated vertical-flow tube. The experimental results indicate that the heat transfer characteristics at the various mass flow rates have marked difference. Heat transfer deterioration (HTD) is not observed at the low-mass flow rate (G = 80–120 kg/(m2·s)) even with a higher q/G. While the obvious HTD is detected in moderate (G = 120–180 kg/(m2·s)) and high (G > 180 kg/(m2·s)) mass flow rate. HTD occurs firstly near the outlet of test section at moderate mass flow rate (where the bulk fluid temperature exceeds the pseudo-critical temperature), and it moves toward the upstream of the test section as the mass flow rate increases. The laminarization of the low-density fluid layer in the heated surface is an important mechanism of HTD. Based on the wall-to-bulk temperature differences generating the modification of properties gradient and shear stress, the impacts of properties gradient, buoyancy effect and flow acceleration as well as the laminarization of the low-density fluid layer on heat transfer are considered in dimensionless form. Consequently, a new correlation is developed based on the heat transfer data more than 2800 which sets from 10 independent experiments.